Lowering maintenance immune suppression in elderly kidney transplant recipients; connecting the immunological and clinical dots - Betjes, Michiel G. H.; De Weerd, Annelies (Frontiers in Medicine, 2023)
The management of long-term immune suppressive medication in kidney transplant recipients is a poorly explored field in the area of transplant medicine. In particular, older recipients are at an increased risk for side effects and have an exponentially increased risk of infection-related death. In contrast, an aged immune system decreases the risk of acute T-cell-mediated rejection in older recipients. Recent advances in alloimmunity research have shown a rapid and substantial decline in polyfunctional, high-risk CD4+ T cells post-transplantation. This lowers the direct alloreactivity responsible for T-cell-mediated rejection, also known as donor-specific hyporesponsiveness. Chronic antibody-mediated rejection (c-aABMR) is the most frequent cause of kidney graft loss in the long term. However, in older adults, c-aABMR as a cause of graft loss is outnumbered by death with a functioning graft. In addition, DSA development and a diagnosis of c-aABMR plateau ~10 years after transplantation, resulting in a very low risk for rejection thereafter. The intensity of immune suppression regimes could likely be reduced accordingly, but trials in this area are scarce. Tacrolimus monotherapy for 1 year after transplantation seems feasible in older kidney transplant recipients with standard immunological risk, showing the expected benefits of fewer infections and better vaccination responses.